Economic Crises and Terrorism: Analyzing Competing Economic Pressures on Terrorism in Russia. Issue 3 (12th September 2020) - Omelicheva, Mariya; Webb, Clayton
Abstract: The prevailing academic consensus holds that economic hardship does not motivate terrorism. We argue that this academic consensus is misguided because it assumes a single causal pathway connecting the economy to terrorism. In addition, most tests rely on national-level macroeconomic measures of economic performance that are not well suited to capturing individual-level decision-making processes that motivate people to engage in political violence. We argue that shifts in economic performance have heterogeneous effects on terrorist activity. The suffering caused by economic hardship energizes pre-existing grievances and generates feelings of anger and resentment toward the government, making affected individuals susceptible to violent radicalization. Economic crises also increase opportunities for terrorist recruitment by weakening institutions for coping with the consequences of sharp economic downturns. On the other hand, the economic losses caused by crises reduce the resources available to terrorist groups. These competing pressures are difficult to observe at the national level and are not equally reflected in all measures of economic performance. We test these arguments using a novel dataset of terrorist attacks and terrorist crimes in the Russian federal subjects between 2008 and 2016. We find evidence to support opportunity- and resource-based arguments for terrorism. These findings suggest a need to rethink the academic consensus on terrorism and a need to problematize the theoretical and empirical approaches that brought us to the prevailing consensus.